The barracudina genera Lestidium and Lestrolepis of Taiwan, with descriptions of two new species (Aulopiformes: Paralepididae) - Ho, Hsuan-Ching; Tsai, Song-Yu; Li, Hsing-Hui (Zootaxa, 2019)
Two genera of barracudinas with luminescent duct in abdominal cavity, Lestrolepis and Lestidium, collected from around Taiwan are studied. Two species in each genus are recognized in Taiwan, including one new species in each genus. New diagnostic characters are used to distinguish these species. Lestrolepis nigroventralis sp. nov. is similar to Lestrolepis intermedia and can be distinguished by having 32–35 prehaemal vertebrae; dorsal-fin origin slightly in front of midline of distance between origins of pelvic and anal fins, distance between origins of dorsal and pelvic fin 9.8–11.7% SL; and pelvic-fin origin at or slightly behind midline of body, prepelvic length 50.6–52.6% SL. Lestidium orientale sp. nov. is similar to Lestidium atlanticum and can be distinguished by having prehaemal vertebrae 37–40; caudal vertebrae 41–44; a relatively short and deep head, reflected by a shorter snout (9.7–10.4% SL), shorter upper jaw (8.6–10.1% SL), shorter lower jaw (11.9–13.7% SL) and a deeper head (31.2–33.9% HL). Data of Lestrolepis japonicus and Lestidium prolixium collected from Taiwan, as well as two Atlantic congeners, are provided. DNA barcoding is conducted to support the recognition of these new species.